Natural polyphenols down-regulate universal stress protein in Mycobacterium tuberculosis: An in-silico approach - M Vijey Aanandhi; Debojit Bhattacherjee; P Samuel Gideon George; Anirban Ray (Wolters Kluwer Medknow Publications, 2014)
Universal stress protein (USP) is a novel target to overcome the tuberculosis resistance. Our present study enlightens the possibilities of some natural polyphenols as an antioxidant for USP. The study has shown some molecular simulations of some selected natural antioxidants with USP. We have considered USP (Rv1636) strain for homology modeling and the selected template was taken for the docking study. Curcumin, catechin, reservetrol has shown ARG 136 (1.8Ε) hydrogen bonding and two ionic bonding with carboxyl group of curcumin with LEU 130 (3.3Ε) and ASN 144 (3.4Ε) respectively. INH was taken for the standard molecule to perform molecular simulation. It showed poor binding interaction with the target, that is, −5.18 kcal, and two hydrogen bonding with SER 140 (1.887Ε), ARG 147 (2.064Ε) respectively. The study indicates possible new generation curcumin analogue for future therapy to down-regulate USP.